The Distribution of Service Rights Using Civic Pluralism Approach: A Case of Penghayat Kepercayaan in Ponorogo Regency - Harda Armayanto; Maria Ulfa; Adib Fattah Suntoro; Indra Indra (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2023)
This research examines the distribution of service rights for Penghayat Kepercayaan adherents in Ponorgo. This region is important because it was the venue for the 5th Indonesian Kebatinan Congress in June 1963. Through the approach of civic pluralism, especially related to the politics of redistribution, this research wants to analyze the problem of distribution of service rights for education, marriage, and death services for Penghayat Kepercayaan adherents in Ponorogo Regency, East Java. This is important because among the main elements of the idea of civic pluralism are state policies and social consensus at the community level to respond to differences and resolve frictions between communities that inevitably arise due to differences between them. This research is qualitative with library and field data collection techniques. The data collected is then analyzed using descriptive analysis method. The result of this research shows that the distribution of service rights of Penghayat Kepercayaan in Ponorogo has not been effective. There are internal and external factors related to this. Among these internal factors are: the individuals of the Penghayat Kepercayaan who are difficult to expose themselves; the fear of being alienated by their communities who adhere to other religions; and the lack of organizational awareness for the youth of Penghayat. These internal factors consequently impact external factors, whereby the Ponorogo Regency Government struggles to distribute service rights for Penghayat Kepercayaan in the fields of education, marriage, and death services.